Using MyLinE Online resources as a platform to develop university students· academic writing skills - Ting, Su Hie; Puteh, Fatimah (2010)
Conventional academic reading and writing courses are usually paper-based with many readings, exercises and writing. Nowadays with technological advancements and students penchant for internet usage, an evolution in teaching materials to include online resources is taking place. One of the readily available online language resources is MyLinE (Online Resources for Learning in English) developed by Universiti Teknologi Malaysia and supported by the Ministry of Higher Education for use in institutions of higher learning in Malaysia. This study examined how MyLinE resources facilitate transfer from informal to formal discussion issues in an academic reading and writing courses. The specific aspects studied were the initial generation of ideas to pooling of ideas, and changes in formality of the language used in the written texts. Data for the study were discussion texts written by undergraduates in an academic reading and writing course in a Malaysian university. Analysis of the undergraduates' discussion on a given issue and the discussion text they wrote, both online, showed that they progressed from expressing single ideas to discussing other views. In addition, the comparison of the semi-spoken and written discussion texts indicated changes in word choice, use of nominalisations and objectivisation of views expressed. The findings suggest that the undergraduates were able to adapt their language to context and the MyLinE resources enhanced the teaching-learning environment by giving quiet students a voice in the language class.